Calyceal Diverticulum: A Case Report - Wibowo, Dwi Nanda Satriyo Arif (Folia Medica Indonesiana, 2021)
Calyceal diverticulums are often benign and asymptomatic. On the other hand, some interventions are necessary in several symptoms. Radiological imaging is performed to made dianoses, but somehow can pose misinterpretation of radiological imaging results and mistreatment from the urologist. To present a case of a calyceal diverticulum treated with open diverticulectomy. This study reported a case of a calyceal diverticulum in a 30-year-old man with an almost 1-month history of left flank pain. The patient undergone several imaging diagnostics, before finally diagnosed calyceal diverticulum with a stone inside it. The patient had underwent open diverticulectomy. Initially, cystoscopy and insertion of Double J Stent (DJ Stent) were done, and then using the lumbotomy approach the incision that had been made. This case demonstrated the use of imaging combined with urologist interpretation and surgical management which was successfully treated the patient's clinical problems.